If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + x + 9 = 95 Reorder the terms: 9 + x + x = 95 Combine like terms: x + x = 2x 9 + 2x = 95 Solving 9 + 2x = 95 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 2x = 95 + -9 Combine like terms: 9 + -9 = 0 0 + 2x = 95 + -9 2x = 95 + -9 Combine like terms: 95 + -9 = 86 2x = 86 Divide each side by '2'. x = 43 Simplifying x = 43
| 3(x-2)+x+4=2(x-1) | | 2(1-11n)+11=-8(n+1)-7 | | -4x+7=27 | | -2a+40+9a=4a-7a | | x^2*5y^4= | | 4(3y+-1)+13=5y+2 | | 6b=6 | | x^2*5y^2= | | 7[200]+12x=1736 | | 2.5x+2=4x+5 | | 4(3y-10)+13=5y+2 | | x^3-8x-6=0 | | 15x-4=2x+9 | | x+10=x | | 4ax^4-22ax^2+10a= | | 2x+5+7x=32 | | -5x+x+3=-13 | | 14=8x+2y | | -(3+4)=6z-3(3z+2) | | 0=16t^2-96t-112 | | 15-(x-2)= | | -12(6x+9)=-6(x+7) | | -3(-2y+3)-(4y-3)+5y+9= | | 6(2x-3)-8x=4x-2 | | 12x+7+x=20 | | 15=15-7c | | -3(2x-4)+8x-4= | | 4a^2-21a+5= | | (3*6/2)v+10=9v+9 | | 12x-10=-6x+14 | | 2m=-18-5 | | 2m=-12-5 |